Progressive-guided inquiry in chemistry effects on students' self-efficacy and knowledge-building practices - Pineda, Laurice A. (College of Education, University of the Philippines Diliman, 2019)
The study investigated the effects of progressive-guided inquiry on students' self-efficacy and knowledge-building practices in Chemistry. In addition, the research investigated whether students' self-efficacy can positively and significantly predict knowledge-building practices, and vice versa. This research also determined the knowledge-building practices of high school chemistry students and presented theses as a taxonomy of knowledge-building practices. A summary model of the practices and subskills was also presented.